Reprogrammed fecal and mucosa-associated intestinal microbiota and weakened mucus layer in intestinal goblet cell- specific Piezo1-deficient mice - Liu, Ying; Fang, Feifei; Xiong, Yilin; Wu, Jiandi; Li, Xueyan; Li, Gangping; Bai, Tao; Hou, Xiaohua; Song, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Dysfunction of the mucus layer allows commensal and pathogenic microorganisms to reach the intestinal epithelium, thereby leading to infection and inflammation. This barrier is synthesized and secreted by host goblet cells. Many factors that influence the function of goblet cells (GCs) have been studied. However, how the microenvironment surrounding GCs influences the mucus layer and microbiota of the colon is unclear. To explore the effect of GC Piezo1 on the mucus layer and microbiota in the colon, we generated an intestinal epithelial Piezo1 conditional knockout mouse model. The fecal-associated microbiota (FAM) and mucosa-associated microbiota (MAM) of the two groups were characterized based on amplicon sequencing of the 16S rRNA gene. Our results showed that GC Piezo1-/- mice developed decreased GC numbers, thinner mucus layer, and increased inflammatory cytokines (e.g., CXCL1, CXCL2, IL-6) on the 7th day. In addition, decreased Spdef and increased DOCK4 were discovered in KO mice. Meanwhile, the diversity and richness were increased in MAM and decreased in FAM in the GC Piezo1-/- group compared with the GC Piezo1+/+ group. We also observed increased abundances of Firmicutes and decreased abundances of Verrucomicrobiota and Actinobacteriota in the MAM of the GC Piezo1-/- group. Additionally, BugBase predicts that potentially pathogenic bacteria may have increased in the inner mucus layer, which is consistent with the higher abundance of Helicobacter hepaticus, Lactobacillus johnsonii, Escherichia-Shigella and Oscillospiraceae in MAM. These results further support the hypothesis that the role of Piezo1 in GCs is important for maintaining the function of the mucus layer and intestinal microbiota balance in the mouse colon.